Genetic and Functional Properties of the Self-Transmissible Yersinia enterocolitica Plasmid pYE854, Which Mobilizes the Virulence Plasmid pYV - Hammerl, Jens A. (American Society for Microbiology (ASM), 2008)
Yersinia strains frequently harbor plasmids, of which the virulence plasmid pYV, indigenous in pathogenic strains, has been thoroughly characterized during the last decades. Yet, it has been unknown whether the nonconjugative pYV can be transferred by helper plasmids naturally occurring in this genus. We have isolated the conjugative plasmids pYE854 (95.5 kb) and pYE966 (70 kb) from a nonpathogenic and a pathogenic Yersinia enterocolitica strain, respectively, and demonstrate that both plasmids are able to mobilize pYV. The complete sequence of pYE854 has been determined. The transfer proteins and oriT of the plasmid reveal similarities to the F factor. However, the pYE854 replicon does not belong to the IncF group and is more closely related to a plasmid of gram-positive bacteria. Plasmid pYE966 is very similar to pYE854 but lacks two DNA regions of the larger plasmid that are dispensable for conjugation.